Blind spots eaudiobook When medicine gets it wrong, and what it means for our health. - Makary, Marty (Bloomsbury Publishing, 2024)
Bloomsbury presents Blind Spots written and read by Dr Marty Makary From Johns Hopkins medical expert Dr. Marty Makary, the New York Times- bestselling author of The Price We Pa y — an eye-opening look at the medical groupthink that has led to public harm, and what you need to know about your health. More Americans have peanut allergies today than at any point in history. Why? In 2000, the American Academy of Pediatrics issued a strict recommendation that parents avoid giving their children peanut products until they're three years old. Getting the science perfectly backward, triggering intolerance with lack of early exposure, the US now leads the world in peanut allergies—and this misinformation is still rearing its head today. How could the experts have gotten it so wrong? Dr. Marty Makary asks, Could it be that many modern-day health crises have been caused by the hubris of the medical establishment? Experts said for decades that opioids were not addictive, igniting the opioid crisis. They refused menopausal women hormone replacement therapy, causing unnecessary suffering. They demonized natural fat in foods, driving Americans to processed carbohydrates as obesity rates soared. They told citizens that there are no downsides to antibiotics and prescribed them liberally, causing a drug-resistant bacteria crisis. When modern medicine issues recommendations based on good scientific studies, it shines. Conversely, when modern medicine is interpreted through the harsh lens of opinion and edict, it can mold beliefs that harm patients and stunt research for decades. In Blind Spots , Dr. Makary explores the latest research on critical topics ranging from the microbiome to childbirth to nutrition and longevity and more, revealing the biggest blind spots of modern medicine and tackling the most urgent yet unsung issues in our $4.5 trillion health care ecosystem. The path to medical mishaps can be absurd, entertaining, and jaw-dropping—but the truth is essential to our health.